Cessna Citation X Business Aircraft Eigenvalue Stability– Part 1: a New GUI for the LFRs Generation - Yamina BOUGHARI; Ruxandra Mihaela BOTEZ; Florian THEEL; Georges GHAZI (INCAS Bulletin, 2017)
The aim of “Robustness Analysis” is to assess aircraft stability in the presence of all admissible uncertainties. Models that are able to describe the aircraft dynamics by taking into account all uncertainties over a region inside the flight envelope have therefore been developed, using Linear Fractional Representation (LFR). In this paper Part 1 a friendly Graphical User Interface is developed to facilitate the generation of Linear Fractional Representation uncertainty models for the Cessna Citation X aircraft using 12 weight and Xcg configurations; thus, 26 regions of the flight envelope are developed for different Weight/ Xcg configurations to study the aircraft’s longitudinal motion. In the aim to analyzed the robustness stability of Cessna Citation X in Part 2 using the Graphical User Interface developed in the Clearance Of Flight Control Laws Using Optimization (COFCLUO) project. This project aimed to boost the aircraft safety using computer computation.